THE APPLICATION OF ARTIFICIAL INTELLIGENCE IN HEALTHCARE: DIAGNOSTIC POTENTIAL, LEGAL FRAMEWORK AND ETHICAL CHALLENGES - Vukadinović Marković, Jelena R.; Kambovski, Igor (Srpska politička misao, 2025)
Artificial intelligence (AI) has assumed an increasingly significant role in contemporary society, particularly within the healthcare sector. While the medical community was initially hesitant to embrace advanced technologies, recent years have witnessed a rapid expansion in the integration of AI into clinical practice. This development has the potential to fundamentally reshape the ways in which diseases are diagnosed, treated, and predicted. Given that the fight against malignant diseases constitutes one of the European Union’s central health policy priorities, as articulated in the strategic document Europe’s Beating Cancer Plan, this paper explores the potential of AI to advance the objectives of that agenda, with particular emphasis on enhancing screening programmes and fostering the development of personalised therapeutic approaches. The paper is organised into three thematic sections. The first section adopts an empirical approach to investigate the potential of AI in a clinical context, with a particular focus on improving diagnostic accuracy and advancing predictive analytics. The second section employs a comparative legal methodology to analyse the regulatory frameworks governing the application of AI in the healthcare systems of the Republic of Serbia and the Republic of North Macedonia. The third section addresses key ethical challenges, including the protection of patient privacy, the mitigation of algorithmic bias, and the safeguarding of informed consent in a technology-mediated medical environment. The methodological framework of this paper is primarily grounded in qualitative analysis, encompassing both legal instruments and relevant professional and academic literature, while incorporating quantitative evidence to the extent that it is available through existing medical research.